2005
DOI: 10.1093/toxsci/kfj067
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an In Vitro High-Throughput Screening Assay for Detecting Phospholipidosis-Inducing Potential

Abstract: Excessive accumulation of phospholipids results in phospholipidosis (PL), which may interfere with cellular functions, leading to acute or chronic disease or even death. Electron-microscopic detection of cytoplasmic lamellar bodies is often used as a diagnostic criterion of PL, but a faster, more convenient procedure is required for high-throughput assay of the PL-inducing potential of candidate drugs. We have developed a 96-well microplate cell-culture method for detecting PL, using a phosphatidylcholine-conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 11 publications
2
66
1
Order By: Relevance
“…The same cutoff val- ue (1.5-fold) was also reported by Bauch et al (2015) using HepG2 and H9c2 cells. In addition, the relationship between concentrations of PLD-positive compounds and fluorescence intensity of phosphatidylcholine-conjugated dye taken up by CHO-K1 cells was investigated by Kasahara et al (2006). Kasahara et al (2006) reported that the minimum positive concentrations for the PLD assay were 10 μM (13.8 μM in our assay) in amiodarone, 10 μM (11 μM in our assay) in chlorpromazine, 10 μM (5.9 μM in our assay) in imipramine, 3 μM (6.8 μM in our assay) in tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same cutoff val- ue (1.5-fold) was also reported by Bauch et al (2015) using HepG2 and H9c2 cells. In addition, the relationship between concentrations of PLD-positive compounds and fluorescence intensity of phosphatidylcholine-conjugated dye taken up by CHO-K1 cells was investigated by Kasahara et al (2006). Kasahara et al (2006) reported that the minimum positive concentrations for the PLD assay were 10 μM (13.8 μM in our assay) in amiodarone, 10 μM (11 μM in our assay) in chlorpromazine, 10 μM (5.9 μM in our assay) in imipramine, 3 μM (6.8 μM in our assay) in tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro models for predicting drug-induced PLD have been developed using various cells such as HepG2 cells (Kasahara et al, 2006;Tilmant et al, 2011;van de Water et al, 2011), human primary hepatocytes (Gum et al, 2001;Kasahara et al, 2006), and rat primary hepatocytes (Gum et al, 2001;Kasahara et al, 2006;Takagi et al, 2016). However, the HepG2 cell line is devoid of a substantial and variable set of liver-specific functions, particularly the major cytochrome P450s (CYPs) that are involved in xenobiotic metabolism (Guguen-Guillouzo and Guillouzo, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An independent test found that based on these genes it is possible to obtain reliable predictions for the PPL potential of drugs [52]. High-throughput screening with cell-based assays represents an effective tool to evaluate large sets of compounds in the preclinical stages to determine their PPL potential [53]. A high-throughput physicochemical assay for PPL screening in early phases of drug discovery is based on the measurement of drug-phospholipid complex formation observed by their effect on the critical micelle concentration of a short-chain acidic phospholipid [54].…”
Section: Drugs With Phospholipidosis Inducing Potentialmentioning
confidence: 99%
“…Although the relationship between DIPL and adverse effects in humans remains unknown, it is necessary to consider toxicity triggered by DIPL in humans. Some studies regarding in vitro screening to avoid DIPL have been reported (Sawada et al, 2005;Kasahara et al, 2006;Morelli et al, 2006;Zhou et al, 2011;Takagi et al, 2016). However, to evaluate DIPL in experimental animals, it is important to consider species differences, organ selectivity, and affinity for phospholipids.…”
Section: Introductionmentioning
confidence: 99%